Special Approach for Thermal Modelling Fibre-Reinforced Composites with Larger Aspect Ratio - Milan Zmindak; Pavol Novak (Communications, 2012)
Fundamental solutions and their derivatives located along fibre axes are presented to simulate the interactions of matrix and reinforcing elements in composite materials, when the primary field is a scalar function temperature in heat conduction. The inter-domain continuity is specified in discrete points on fibres boundaries. Intensities of the source functions are defined by 1D NURBS (Non-Uniform Rational Basis Spline) and computed in LS (Least Square) sense in the fibres. The inter-domain continuity equations have to be completed by balance equations (energy, equilibrium, etc.) in order to obtain temperature in centre of each fibre. Gradients of temperature are supposed to be constant in cross-sections of the fibres and are computed iteratively by considering them to be linear along fibres in the first step. Material properties of both matrix and fibres are assumed to be homogeneous and isotropic. Three numerical examples giving two fibres overlapping in some lengthin infinite matrix show the numerical behaviour of the problem for heat conduction.